Analisis pengaruh service recovery terhadap loyalitas pelanggan dalam jasa telepon seluler - Antika, Mia; Kussudyarsana, Kussudyarsana; Hananti, Evita Dhewi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2017)
The objectives of this research is to examine the impact of service recovery toward trust, and customer loyalty. To look at the connection between service recovery and customer loyalty this research used justice perspective that included procedural justice, interactional justice and distributive justice. The setting of this research was information technology business. The research was conducted in area of Surakarta regency with the customer phone operator as research respondent. This research used convinience sampling and employed 150 respondent that grouped by complaint and non-complaint customer. Regression analysis was used in this research to analyse the data. Research indicated that procedural justice have significant impact toward customer satisfaction. In contrast, distributive and interactional justive did not significant impact toward customer satisfaction. This research also found that trust and customer satisfaction significantly impact toward trust and customer loyalty. In addition, this result found that non-complaint respondent were more trust and loyalty than customer who complaint to service which provided by phone operator. This indicated that service recovery did not enable to recover service failure.